2022
DOI: 10.3389/fmicb.2022.808890
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing and Antifungal Susceptibility of Vaginal and Non-vaginal Candida glabrata Isolates From China

Abstract: Candida glabrata is a common cause of Candida infections. In our present study, we investigated the antifungal susceptibility and molecular epidemiology of vaginal and non-vaginal C. glabrata isolates. Seventy-six vaginal C. glabrata strains isolated from patients with vulvovaginal candidiasis and 57 non-vaginal C. glabrata isolates were collected at two hospitals in Shanghai, China. Antifungal susceptibility was examined using a broth microdilution method. Multilocus sequence typing was used for genotyping. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…isolates have mostly been carried out by employing MLST or MLMT-based methods (28-31, 34, 41-43). Although MLST schemes were devised for C. albicans (44) and C. glabrata (26) at nearly the same time, extensive studies have been carried out on clinical C. albicans isolates while only few studies have explored the population structure of C. glabrata (28,31,(45)(46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…isolates have mostly been carried out by employing MLST or MLMT-based methods (28-31, 34, 41-43). Although MLST schemes were devised for C. albicans (44) and C. glabrata (26) at nearly the same time, extensive studies have been carried out on clinical C. albicans isolates while only few studies have explored the population structure of C. glabrata (28,31,(45)(46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…C. glabrata is among the most frequently isolated NACS from clinical specimens in Kuwait (17,18) (53) from China. The higher genetic diversity of C. glabrata from Kuwait, an Arabian Gulf country much smaller than Australia, Iran or Tanzania, is likely due to the large (nearly three times of Kuwaiti nationals) and highly diverse expatriate population (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, like most other studies looking at the species distribution of Candida , the most prevalent Candida species isolated was C. albicans , followed by C. glabrata [ 47 , 48 ]. Candida glabrata is the most relevant non-albicans Candida species, owing to its ability to develop acquired resistance subsequent to exposure to azole antifungals [ 11 , 12 , 49 ]. In our study, low rate of fluconazole resistance was found in C. albicans isolates (< 5%), but most non-albicans Candida isolates ( n = 19, 17%) were fluconazole resistant.…”
Section: Discussionmentioning
confidence: 99%
“…Non-albicans Candida species have emerged as an important aetiology of VVC as its prevalence and antifungal resistance is a mounting problem globally [ 10 , 11 ]. The most significant of these non-albicans Candida species is Candida glabrata owing to its intrinsic resistance or low susceptibility to azoles [ 12 ]. Other than C. glabrata , C. krusei, C. tropicalis, C. parapsilosis and, very rarely, Saccharomyces cerevisiae , are other potential pathogens that may lead to VVC [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…[18,19]). However, since 2003, multilocus sequence typing (MLST) has been the main method for genotyping and for investigating the spatial and temporal patterns of genetic variation in C. glabrata [20][21][22][23][24]. These studies have revealed contrasting patterns, such as low genetic relatedness in isolates recovered from the same geographical region as well as highly similar genotypes among distant locations.…”
Section: Introductionmentioning
confidence: 99%